Exploring the mechanism of consumer purchase intention in a traditional culture based on the theory of planned behavior - Zong, Zupan; Liu, Xinyu; Gao, Huijing (Frontiers in Psychology, 2023)
Given the importance of cultural empowerment, there has been a growing interest among scholars and practitioners. By doing so, this study aims to explore the connection between traditional cultural symbols and cultural identity, and how to the two stimulate consumers' emotional value to generate consumers' purchase intention. Based on existing traditional cultural literature and theory of planned behavior (TPB), we proposed a research framework and empirically tested the relationship among traditional culture symbols, cultural identity, emotional value, and consumers' purchase intention. The survey data was tested using structural equation modeling (SEM) and the following conclusions were drawn. Frist, the cognition of traditional cultural symbols and cultural identity have a direct and significant impact on the emotional value thereby, eliciting consumers' purchase intention. Second, traditional cultural symbols are directly and indirectly (i.e., through emotional value) positively associated with consumers' purchase intention, but cultural identity is indirectly associated with consumer purchase intention. Finally, emotional values mediate the indirect effect of traditional culture and cultural identity on purchase intention. Our findings help to expand the existing literature on consumer purchase intentions by rationally using traditional cultural symbols in the product design and suggesting relevant marketing strategies. The research results can provide valuable inspiration for promoting the sustainable development of the national tidal market and repeating consumers' purchasing intentions